Life table of Xylocoris afer (Hemiptera: Anthocoridae) feeding on eggs of Corcyra cephalonica (Lepidoptera: Pyralidae) and Plutella xylostella (Lepidoptera: Plutellidae) - Vieira, Natalia Fernanda [UNESP]; Truzi, Caio Cesar [UNESP]; Veiga, Ana Carolina Pires; Sipriano-Nascimento, Thamiris Porto [UNESP]; Vacari, Alessandra Marieli; De Bortoli, Sergio Antonio [UNESP] (Elsevier, 2018)
The aim was to evaluate the biological aspects of Xylocoris afer fed on Corcyra cephalonica and Plutella xylostella eggs. The experiment was conducted with X. afer nymphs aged 12–24 h, one per Petri dish, resulting in a total of 60 nymphs (60 repetitions). On each dish, we placed P. xylostella and C. cephalonica eggs daily, together with a cotton roll moistened with distilled water and conducted daily evaluations. We evaluated the duration, viability, and consumption of nymphal stages, the longevity of males and females, the number of eggs per female, and egg fertility. In addition, the biological data were used to determine the parameters of the fertility life table. The consumption by adults (male and female) of X. afer differed between the preys, the highest consumption was C. cephalonica eggs. Females that consumed eggs of C. cephalonica produced about 90% more eggs and more offspring than those that fed on P. xylostella eggs. Based on our results, it can be inferred that the predator completed its development feeding both on natural prey and the alternative, evidencing the possible potential of X. afer to be used in the biological control of P. xylostella as well as the use of C. cephalonica in mass rearing of this predator under laboratory conditions, aiming its use in applied biological control. However, before being accepted for biological control agent against agricultural pests, various factors should be examined in ecosystem level, as the behavior of predator in different densities of prey.
Keywords: Biology; Diamondback moth; Natural enemy; Predator; Rice meal moth